Original articleValue of Doppler ultrasonography in renal artery stenosis recognition - Kabłak-Ziembicka, Anna; Przewłocki, Tadeusz; Tracz, Wiesława; Kopeć, Grzegorz; Kostkiewicz, Magdalena; Pieniążek, Piotr; Kozanecki, Artur; Rzeźnik, Daniel; Stompor, Tomasz; Sułowicz, Władysław (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2006)
The purpose of this study was to investigate the accuracy of renal angiography and Doppler ultrasonography (DU) flow parameters in detection of renal artery stenosis (RAS). Methods: 420 (286 M) patients, aged 63.6±9.6 y. underwent renal DU with the assessment of: peak systolic (PSV), end-diastolic (EDV) velocity in the renal artery, renal aortic ratio (RAR) and resistance index (RI). Intrarenal parameters were also assessed: acceleration (Acc), acceleration time (AT), difference in intrarenal resistance indices (DIRI) and length difference between kidneys. Results: On quantitative angiography, in 265 patients RAS was <30% lumen stenosis, in 70 patients it was between 30 and 49%, in 79 patients it was ł50%, and in 6 patients renal artery occlusion was found. The grade of RAS correlated significantly with PSV (r=0.720, p<0.001), RAR (r=0.718, p<0.001), kidney length difference (r=0.391, p<0.001), DIRI (r=–0.359, p<0.001), AT (r=0.447, p<0.001) and Acc (r=–0.534, p<0.001). Extracranial flow parameters differed significantly between patients with RAS <30% and RAS 30-49%, and between patients with RAS 30-49% and RAS ≥50%. Renal size, mean DIRI, and AT values were all decreased significantly (p<0.001) only for RAS ł50% compared with values in patients with RAS 30-49% and <30%. The best performing parameters for RAS ≥50% were revealed to be PSV, RAR, AT and kidney length difference. Cutoff values for PSV of 2.06 m/sec, for RAR of 2.71 and for AT of 93 msec provided the best predictive value with a sensitivity of 91.1%, a specificity of 94.3%, and positive and negative predictive values of 79.1% and 97.8%. Conclusions: DU with analysis of extra- and intrarenal flow is recommended as a useful method for noninvasive diagnosis and grading of RAS.